Generalizable safety annotations for specification of failure patterns - Papadopoulos, Yiannis; Walker, Martin; Grunske, Lars; Wolforth, Ian (Software-Practice & Experience, 2010)
Components in programmable systems often exhibit patterns of failure that are independent of function or system context. In this paper, we show that it is possible to capture, and reuse where appropriate, such patterns for the purposes of system safety analysis. We describe a language that enables abstract specification of failure behaviour and define the syntax and semantics of this language. The language extends concepts originally defined in HiP-HOPS, a technique that enables a largely automated form of compositional system safety analysis. The paper describes how this language can be used to describe component failure patterns and demonstrates how it can be applied using a simple fuel system example. The approach is evaluated on a set of retrospective industrial case studies, where data-mining and reverse engineering techniques are applied in order to identify hidden patterns in legacy safety analyses. Results show clear potential for practical use of patterns in HiP-HOPS. We argue that careful specification and reuse of failure patterns in conjunction with a tool that automates Fault Tree and Failure Modes and Effects Analysis can help to simplify complex safety assessments. Copyright (c) 2010 John Wiley & Sons, Ltd.
Keywords: Software